Juridical Analysis of Implementation of Public Service Standards in the Service of Population and Civil Registration in Magetan District - Fransiskawati, Enny; Anwar, Saiful; Fadhli, Muhibuddin (International Journal of Law and Society, 2023)
Public service is an activity in which there is fulfillment of service needs in accordance with applicable regulations, because there are laws that regulate it, the community or residents have rights to goods or services and other administrative services that have been provided by public service providers. The purpose of this research is to be able to find out how the implementation of statutory regulations regarding the implementation of public service standards and what are the obstacles faced in public services. This writing uses the type of empirical legal research. This research is carried out by looking at the facts in the field where the contents of the research include understanding and studying how to apply the law directly to the subject of the field. The results and conclusions of this study are that the implementation of laws and regulations regarding the application of public service standards for the Population and Civil Registration Office of Magetan Regency has implemented the law well marked by the absence of problems with the community, although in conclusion it cannot be fully stated that the Magetan Population and Civil Registration Agency has universally implemented law but in one subject this can be said as a public service provider is already a very good thing.